The Effects of Exercise Training on Exercise Capacity and Vascular Function after Transcatheter Aortic Valve Implantation—A Pilot Study - Luka Vitez; Matjaž Bunc; Borut Jug (Journal of Cardiovascular Development and Disease, 2023)
Transcatheter aortic valve implantation (TAVI) improves event-free survival in patients with severe aortic stenosis, but patients’ exercise capacity remains poor after the procedure. Therefore, we sought to compare the effects of a supervised center-based exercise training program and unsupervised exercise routine on exercise capacity and vascular function in patients after TAVI. Patients were randomized to either center-based exercise training (12–24 sessions of combined aerobic and low-weight resistance training twice weekly for 8–12 weeks) or an unsupervised home-based exercise routine (initial appraisal with detailed recommendations and monthly follow-up). Exercise capacity (cardiopulmonary testing) and vascular function (ultrasonographic measurement of flow-mediated vasodilation (FMD) and arterial stiffness) were assessed at the baseline and after the study period. We included 23 patients (mean age of 81 years, 61% women), with higher-than-expected drop-out rates (41%) because of the coronavirus-19 pandemic outbreak. Exercise capacity improved over time, irrespective of the intervention group: 0.09 mL/min/kg increase in peak oxygen uptake (95% CI [0.01–0.16]; p = 0.02), 8.2 Watts increase in workload (95% CI [0.6–15.8]; p = 0.034), and 47 s increase in cumulative exercise time (95% CI [5.0–89.6]; p = 0.029). A between-group difference in change over time (treatment effect) was detected only for FMD (4.49%; 95% CI [2.35; 6.63], p < 0.001), but not for other outcome variables. Both supervised and unsupervised exercise training improve exercise capacity and vascular function in patients after TAVI, with supervised exercise training possibly yielding larger improvements in vascular function, as determined by FMD.